Collaboration of Ezh2 and Runx1 inactivating mutations in malignant haematopoiesis - Booth, C (2017)
Extensive efforts have shed light on the identity and biology of cancer stem cells, required and sufficient for the propagation of hematological malignancies and solid tumours. Much less is understood about the closely related issue as to the identity and properties of the normal stem and progenitor cells targeted by oncogenic lesions, and how the nature of the targeted cell might impact on the biology and clinical picture of the resulting cancer. To address this, we developed a mouse model allowing targeted inactivation of Ezh2 and Runx1 to different haematopoietic compartments. Inactivating mutations of EZH2 and RUNX1 frequently co-occur in haematological malignancies with markedly different phenotypes including myelodysplastic syndrome (MDS) and early thymic progenitor (ETP) leukaemia. Inactivation of Ezh2 and Runx1 in adult haematopoietic stem cells (HSCs) resulted in perturbed haematopoiesis leading to development of an MDS-like disease. Unexpectedly, this MDS phenotype could be fully reproduced when Ezh2 and Runx1 inactivation was targeted to multipotent progenitors (MPPs) using Flt3-Cre. Furthermore, the disease was transplantable by MPPs, but not more committed progenitor populations, demonstrating that MDS tumour propagating potential is not exclusive to intrinsically self-renewing HSCs. Targeting Ezh2 and Runx1 inactivation to early lympho-myeloid progenitors did not result in an MDS phenotype. These mice showed a marked expansion of ETPs within the thymus, combined with a block in thymocyte differentiation. These expanded ETPs displayed transcriptional features characteristic of ETP leukaemia, a treatment-resistant acute leukaemia subtype hypothesised to originate from ETPs. Combination of inactivation of Ezh2 and Runx1 in ETPs with the constitutively activating Flt3-ITD signalling mutation resulted in an aggressive lympho-myeloid acute leukaemia, which could be propagated by the expanded ETP population. These findings demonstrate the potential of lympho-myeloid progenitors such as ETPs to become leukaemia stem cells which propagate a disease retaining lympho-myeloid features. We used this novel ETP leukaemia model to explore therapeutic targeting of Ezh2-inactivated ETP leukaemias using inhibitors of the bromodomain and extra terminal (BET) proteins. Aberrant transcription resulting from epigenetic changes induced by Ezh2 loss could be reversed by BET inhibitors, and these compounds showed therapeutic efficacy against both mouse and human ETP leukaemias in vitro and in vivo.